Hubungan antara Tingkat Kecemasan Ibu Hamil Trimester III dengan Tekanan Darah selama Kehamilan - Novi Yulianti; Susanti, Susanti (PPNI UNIMMAN, 2025)
Background: Anxiety is one of the psychological conditions commonly experienced by pregnant women, especially in the third trimester approaching delivery. Untreated anxiety can affect physiological balance, including increasing the risk of high blood pressure which can develop into complications such as preeclampsia. Objective: This study aims to determine the relationship between anxiety levels and blood pressure in pregnant women in the third trimester. Method: This study used an analytical quantitative design with a cross-sectional approach. The sample consisted of 80 pregnant women in the third trimester selected using a purposive sampling technique at the Fitri Clinic in Batam City. Anxiety level data were collected using the HARS (Hamilton Anxiety Rating Scale) questionnaire, and blood pressure data were obtained through direct measurement and recording from medical records. Bivariate analysis used the Chi-Square test with a significance level of p <0.05. Results: As many as 20% of respondents experienced severe anxiety, and 27.5% had high blood pressure. The results of statistical tests showed a significant relationship between anxiety levels and blood pressure in pregnant women in the third trimester (p = 0.012). Conclusion: There is a significant relationship between anxiety levels and blood pressure during pregnancy. Detection and management of anxiety need to be part of antenatal care services to prevent the risk of pregnancy complications due to increased blood pressure.